(untitled) (Edad Media. Revista de Historia, 2023)
The minutes volume of the notary Gómez González includes numerous obligations for loan consigned between 1448 and 1451 in the city of Avila. The creditors of these obligations are Christians, in some cases recently converted from Judaism, while the margins or headings of the notarial record refers to Jews. This paper examines the social relations between Jews and Christians as credit agents, as well as the mechanisms of debt transfers and subrogation of the creditor’s identity in relation to the legislation regulated the credit market in 15th century Castile.